MECHANISMS FOR PREPARING FOR INNOVATIVE ACTIVITY IN PEDAGOGICAL EDUCATION BASED ON A CLUSTER APPROACH (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the mechanisms for preparing future teachers for innovative activity in pedagogical education through a cluster-based approach. The study proceeds from the idea that the modernization of teacher education requires not only the renewal of curricular content, but also the creation of an integrated educational environment in which higher education institutions, schools, research centers, methodological services, employers, and digital platforms operate as interconnected components of a unified pedagogical cluster. The article analyzes the conceptual foundations of the cluster approach and its potential for strengthening the practical, research, organizational, and technological readiness of students for innovation-oriented professional activity. Special attention is given to the development of institutional cooperation, interdisciplinary integration, mentoring systems, project-based learning, and reflective practices that enable future teachers to respond flexibly to the changing demands of the educational sphere. The paper substantiates that cluster interaction expands opportunities for professional self-development, supports the formation of innovative competence, and increases the adaptability of pedagogical education to contemporary social and educational transformations. The findings indicate that the effectiveness of innovation training depends on coordinated management, resource integration, the continuity of theory and practice, and the establishment of sustainable partnerships among all participants in the pedagogical process. As a result, the cluster approach is interpreted as an effective mechanism for improving the quality of pedagogical education and for fostering teachers capable of designing, implementing, and evaluating educational innovations in diverse professional contexts.
Keywords: Pedagogical education, cluster approach, innovative activity, teacher training, innovative competence, educational integration, professional readiness, project-based learning, pedagogical partnership, educational environment.